Electron Microscopy of Solitary and Aggregated Slime Mould Cells - Mercer, E. H. (The Rockefeller University Press, 1960)
Polysphondylium violaceum and Dictyostelium discoideum myxamoebae have simple double-layered nuclear membranes, a cytoplasmic reticulum of particle-covered membranes, and small mitochondria consisting of convoluted tubules tightly packed in double membranes. In addition to objects still recognisable as bacteria, their food vacuoles contain concentric (or spiral) membranes, apparently formed secondarily from undigested material; these are ultimately ejected. Where the triple-layered plasma membranes (∼70 A wide) of cells in the early aggregates are apposed to one another, they run parallel but separated by a layer of rather constant thickness (∼200 A), as in many unspecialised metazoan tissues. Thus studies on slime moulds may well increase our understanding of cell adhesion and tissue formation in metazoa.